1996
DOI: 10.1002/(sici)1097-0215(19960807)67:4<515::aid-ijc9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Second primary tumors in patients with hereditary retinoblastoma: A register-based follow-up study, 1945–1994

Abstract: The aim of this register-based follow-up study was to evaluate the long-term cumulative incidence of second primary tumors (SPT) among survivors of hereditary retinoblastoma, with special interest for the incidence of pineoblastoma in retinoblastoma patients born after 1970. The Dutch Retinoblastoma Register was completed and updated: in the period 1945-1994, 639 retinoblastoma patients were registered. The vital status of each patient was obtained from the municipal registries and the Central Office of Geneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 16 publications
3
37
2
1
Order By: Relevance
“…The national retinoblastoma register of the Netherlands (Schappert- Kimmijser et al 1966;DerKinderen 1987) was used. For our study, the register has recently been updated and the data verified (Moll et al 1995). We extracted the date of birth of the 941 registered Dutch retinoblastoma patients born during the period from 1862 to 1994 and, if available, the date of birth of their parents.…”
Section: Methodsmentioning
confidence: 99%
“…The national retinoblastoma register of the Netherlands (Schappert- Kimmijser et al 1966;DerKinderen 1987) was used. For our study, the register has recently been updated and the data verified (Moll et al 1995). We extracted the date of birth of the 941 registered Dutch retinoblastoma patients born during the period from 1862 to 1994 and, if available, the date of birth of their parents.…”
Section: Methodsmentioning
confidence: 99%
“…[65] The elevated risk of second primary bladder cancer among retinoblastoma survivors has been attributed to radiation treatment or cyclophosphamide chemotherapy [66][67][68]. However, Fletcher et al, found that hereditary retinoblastoma survivors who were not exposed to highdose radiation or chemotherapy had a substantially higher mortality from bladder cancer versus the general population (standardized mortality ratio [SMR] = 26.3; 95%, CI 8.5-61.4).…”
Section: High-penetrance Genesmentioning
confidence: 99%
“…[58][59][60] The 30-year cumulative incidence for second cancers in bilateral retinoblastoma has been reported at 35% for patients who received radiation therapy compared with 6% for those who did not receive radiation. 59 Abramson and Frank 61 found that external beam radiotherapy increased the incidence of second cancers in the field of radiation but did not stimulate second cancers outside the field of irradiation.…”
Section: External Beam Radiotherapymentioning
confidence: 99%